2019
DOI: 10.3390/su11082399
|View full text |Cite
|
Sign up to set email alerts
|

A Strain-Softening Constitutive Model of Heterogeneous Rock Mass Considering Statistical Damage and Its Application in Numerical Modeling of Deep Roadways

Abstract: During the construction of underground caverns, the stability of deep underground cavern excavation, which affects the safety and sustainable development of such projects, is a hot issue. First, based on the mechanical properties of surrounding rock in deep tunnels, the strain-softening behavior, damage, and heterogeneity of rock masses are analyzed. Then, a strain-softening model of heterogeneous jointed rock mass that considers statistical damage (SSD) is developed and implemented through FLAC3D simulation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…Even for the same rock material, the difference in loading or unloading patterns results in varying mechanical properties for rocks. Universal constitutive models ignore these influences, meaning applications of these universal constitutive models and failure criteria results in large modeling errors, especially under complex loading conditions or stress paths because most universal constitutive models and failure criteria are established based on simple uniaxial loading tests [27]. In this paper, damage factors along the maximum and minimum principle stresses were added into consideration and a constitutive model considering anisotropic damage was proposed.…”
Section: A Constitutive Model and Failure Criterion Of Surrounding Romentioning
confidence: 99%
“…Even for the same rock material, the difference in loading or unloading patterns results in varying mechanical properties for rocks. Universal constitutive models ignore these influences, meaning applications of these universal constitutive models and failure criteria results in large modeling errors, especially under complex loading conditions or stress paths because most universal constitutive models and failure criteria are established based on simple uniaxial loading tests [27]. In this paper, damage factors along the maximum and minimum principle stresses were added into consideration and a constitutive model considering anisotropic damage was proposed.…”
Section: A Constitutive Model and Failure Criterion Of Surrounding Romentioning
confidence: 99%
“…The usage of strain softening model is very important for the simulation of tensile-shear bands. The strain softening model was used to qualitatively and quantitatively analyze the failure of roadway (Cao et al 2019; Guan et al 2020;Li et al 2019;Kang et al 2021;Zhou et al 2009), which showed that the strain softening model can better simulate the dynamic failure characteristics of surrounding rock of roadway. Lu et al (2010) obtained the softening law of post-peak mechanical parameters of weak rock through establishing the subsequent yield surface model of weak rock characterized by two state parameters (generalized cohesion and generalized internal friction angle).…”
Section: Introductionmentioning
confidence: 99%
“…Qin [15] used the method of theoretical analysis and numerical simulation to systematically study the distribution characteristics of the roof bearing structure of the deep soft rock roadway and finally proposed and successfully applied the roof reinforcement scheme of the deep dynamic soft rock roadway. Li [16] analyzed the strain-softening behavior, damage, and heterogeneity of rock masses of the deep roadway, established the strain-softening model of heterogeneous jointed rock mass considering the statistical damage, and successfully applied the model to the engineering practice. Through numerical simulation and similar material test, Qi [17] studied the influence of roof presplitting and rock mass filling on the stability of roadway surrounding rock of deep high stress roadway.…”
Section: Introductionmentioning
confidence: 99%